Morphology of rubber-modified vinyl ester resins cured at different temperatures - Auad, María L. (2003)
The morphologies of styrene (St) crosslinked divinylester resins (OVER) modified with elastomers were analyzed. The primary focus of this study was on the effect of the molecular weight of the resins, the reactivity of the elastomeric modifiers, and the temperature of curing. All of these variables have a strong influence on both the miscibility and the viscosity of the system, affecting the phase-separation process that takes place in the unreacted and the reacting mixture. The selected liquid rubbers were carboxyl-terminated poly(butadiene-co-acrylonitrile) (CTBN), a common toughening agent for epoxy resins, and an almost unreactive rubber with the DVER; and St comonomers and vinyl-terminated poly(butadiene-co-acrylonitrile (VTBN), a reactive rubber. Different morphologies potentially appear in these systems: structures formed by DVER-St nodules surrounded by elastomer and spanning the whole sample; dual cocontinuous micron-size domains formed by elastomer-rich or resin-rich domains; and a continuous DVER-St-rich phase with included complex nodular domains. These microstructures can be varied by just changing the nature and concentration of the elastomer, the molecular weight of the resin, or the curing temperature. The appearance of these morphologies is discussed as a function of the above variables.